Sembapatrimonioimaterial.com: local performances, imagined national narratives, dialogue from the field - Soares, Andre Castro (GIS - Gesture, Image and Sound - Anthropology Journal, 2021)
Developments in semba in Angola, from "live" to "online" performances, and its heritagization, have provoked much discussion among its communities of practice (Wenger-Trayner and Wenger-Trayner 2015) and other imagined communities (Anderson 1983). This article concerns on-going research, based on collaborative work with key interlocutors on the compilation of the website sembapatrimonial.com as a methodological approach. Based on a series of collaborative posts, the interlocutors discuss dissensus (Rancière and Corcoran 2010) in the various visions and versions of heritage in the present, a process of “past-presencing” (Macdonald 2013).